Development of repaglinide loaded solid lipid nanocarrier: Selection of fabrication method - Rawat M.K.; Jain A.; Mishra A.; Muthu M.S.; Singh S. (My University, 2025)
Repaglinide solid lipid nanoparticles (RG-SLN) were fabricated using stearic acid as lipid. Pluronic F68 (PLF68) and soya lecithin were used as a stabilizer. SLNs were prepared by modified solvent injection and ultrasonication methods. SLNs prepared with modified solvent injection method have larger particle size (360±2.5nm) than prepared with ultrasonication method (281±5.3nm). The zeta potential of the prepared formulations by these two methods varied from - 23.10 ±1.23 to -26.01 ±0.89 mV. The maximum entrapment efficiency (62.14 ±1.29%) was obtained in modified solvent injection method. The total drug content was nearly same (98%) in both the methods. In vitro release studies were performed in phosphate buffer (pH 6.8) with 0.5% sodium lauryl sulphate (SLS) using dialysis bag diffusion technique. The cumulative drug release was 30% and 50% within 2 hrs in modified solvent injection and ultrasonication method, respectively. This indicates that RG-SLN prepared from modified injection method released the drug more slowly than SLNs prepared with ultrasonication method. Differential scanning calorimetry indicates that repaglinide (RG) entrapped in the solid lipid nanoparticles (SLN) exist in an amorphous or molecular state. Repaglinide loaded solid lipid nanoparticles prepared with both methods were of spherical shape as observed by transmission electron microscopy (TEM). These results suggest that modified solvent injection method is more suitable for preparation of repaglinide SLNs using stearic acid. © 2010 Bentham Science Publishers Ltd.